Allergy and asthma: Effects of the exposure to particulate matter and biological allergens. Issue 9 (September 2015) - Baldacci, S.; Maio, S.; Cerrai, S.; Sarno, G.; Baïz, N.; Simoni, M.; Annesi-Maesano, I.; Viegi, G.; ,
Abstract: The prevalence of asthma and allergies including atopy has increased during the past decades, particularly in westernized countries. The rapid rise in the prevalence of such diseases cannot be explained by genetic factors alone. Rapid urbanization and industrialization throughout the world have increased air pollution and population exposures, so that most epidemiologic studies are focusing on possible links between air pollution and respiratory diseases. Furthermore, a growing body of evidence shows that chemical air pollution may interact with airborne allergens enhancing the risk of atopic sensitization and exacerbation of symptoms in sensitized subjects. These phenomena are supported by current in vitro and animal studies showing that the combined exposure to air pollutants and allergens may have a synergistic or additive effect on asthma and allergies, although there is an insufficient evidence about this link at the population level. Further research is needed in order to elucidate the mechanisms by which pollutants and biological allergens induce damage in exposed subjects. The abatement of the main risk factors for asthma and allergic diseases may achieve huge health benefits. Thus, it is important to raise awareness of respiratory allergies as serious chronic diseases which place a heavy burden on patients and on society as a whole. Highlights: Rapid rise in allergic diseases cannot be explained by genetic factors alone. Air pollution, biological allergens and their interaction affect allergic diseases. Combined exposure to air and biological pollutants has synergetic effect. Further research is needed to elucidate the mechanism that underlies airways damage. The article should have impact on European policy makers to reduce air pollution.